NAKED IN DEATH - Robb, J. D., 1950- (New York : Berkley, 2020)
Eve Dallas is a New York police lieutenant hunting for a ruthless killer. In over ten years on the force, she's seen it all--and knows her survival depends on her instincts. And she's going against every warning telling her not to get involved with Roarke, an Irish billionaire--and a suspect in Eve's murder investigation. But passion and seduction have rules of their own, and it's up to Eve to take a chance in the arms of a man she knows nothing about--except the addictive hunger of needing his touch.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Young women -- Crimes against -- Fiction; Thrillers (Fiction); Science fiction; Fiction; Mystery fiction